Baccalaureate at Technical University: Problems and Ways of Their Solutions - N. N. Dvulichanskaya; G. N. Fadeev (Moscow Polytechnic University, 2018)
The article explores the state of professional staff training in Russian higher education institutions in the conditions of transition to a two-tier "bachelor - master" system and suggests the ways for improvement of the process of undergraduate technical training in the current situation. The authors present a comparative analysis of foreign and domestic baccalaureate at the present stage and cover the main problems associated with the transition to a two-tier system "bachelor - master". The article substantiates the importance of natural science disciplines in achieving the goal of undergraduate education - the formation of technical bachelor's competences defined by the Federal State Educational Standard of Higher Education. The authors propose the model of undergraduate engineering education aimed at strengthening of its fundamentality based on qualitative education in natural sciences and general technical disciplines. Basing on their own experience, the authors consider the forms and methods of organization of learning the natural science disciplines on the example of teaching chemistry to technical students. These new forms will contribute to improving the quality of undergraduate training at technical university